2021
DOI: 10.1101/2021.06.21.21259104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Models of COVID-19 vaccine prioritisation: a systematic literature search and narrative review

Abstract: Background: How best to prioritise COVID-19 vaccination within and between countries has been a public health and an ethical challenge for decision-makers globally. We systematically reviewed epidemiological and economic modelling evidence on population priority groups to minimise COVID-19 mortality, transmission and morbidity outcomes. Methods: We searched the National Institute of Health iSearch COVID-19 Portfolio (a database of peer-reviewed and pre-print articles), Econlit, the Centre for Economic Policy … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Our ndings are consistent with previous modelling studies which support prioritising vulnerable adults (by age or comorbidity) when vaccine rollout is slow, if vaccine effectiveness against acquisition is low, and/or if community transmission is high [27][28][29][30][31][32]. Our study is one of the rst single-country studies of a low-income country based on a recent review of COVID-19 vaccine prioritisation models [4].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our ndings are consistent with previous modelling studies which support prioritising vulnerable adults (by age or comorbidity) when vaccine rollout is slow, if vaccine effectiveness against acquisition is low, and/or if community transmission is high [27][28][29][30][31][32]. Our study is one of the rst single-country studies of a low-income country based on a recent review of COVID-19 vaccine prioritisation models [4].…”
Section: Discussionsupporting
confidence: 89%
“…As vaccine supplies in low-and middle-income countries (LMIC) begin to increase, vaccine coverage rates are becoming determined by the capacity of countries to rollout vaccine programmes [3]. COVID-19 vaccine rollouts have been modelled extensively in high-income countries (HIC), however there remains limited published literature in LMIC [4]. Vaccine prioritisation strategies from HIC cannot be generalised to LMIC due to differences in age demographics, contact patterns, and seroprevalence between these settings [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this was not evident in our study as the priority group remained the same for the delta variant with a higher reproduction number. As found in some of our scenario analyses, other studies concluded vaccine optimization also depended on the vaccine supply ( 37, 38 ).…”
Section: Discussionsupporting
confidence: 79%
“…(See Appendix A for the full list of 35 of these 55 papers that aren’t cited in this section; see Saadi et al for a more in-depth narrative review of the modeling evidence.) 6 Most studies chose to define COVID-19 vulnerability based on age, which is one of the strongest and most well-known predictors of risk, however age is just one of several criteria that should be considered for targeting. For example, certain underlying medical conditions are associated with a higher risk of hospitalization and/or death from COVID-19.…”
Section: Introductionmentioning
confidence: 99%